1998
DOI: 10.1063/1.121426
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering in ion-implanted GaN

Abstract: Raman measurements were performed on molecular beam epitaxially grown GaN before and after implantation with Ar+, Mg+, P+, C+, and Ca+ ions. With increasing ion dose, new Raman peaks arise at 300, 360, 420, and 670 cm−1, independent of the ion species. After rapid thermal annealing at temperatures between 900 and 1150 °C for 15 s, the intensities of the Raman modes decrease with increasing temperature with the exception of the 360 cm−1 mode which shows a maximum in intensity after annealing at 900 °C. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
115
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(148 citation statements)
references
References 10 publications
32
115
0
1
Order By: Relevance
“…In the previous work on Raman spectroscopy for ionimplanted GaN films, the modes at 290 and 670 cm Ϫ1 appeared in samples implanted with Ar, Mg, P, C, and Ca ions. 19 This means that such modes are independent of the local vibrations of Mn impurities. Therefore, it is believed that these modes at 290 and 670 cm Ϫ1 originated from the macroscopic disorder or vacancy-related defects due to the Mn implantation.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work on Raman spectroscopy for ionimplanted GaN films, the modes at 290 and 670 cm Ϫ1 appeared in samples implanted with Ar, Mg, P, C, and Ca ions. 19 This means that such modes are independent of the local vibrations of Mn impurities. Therefore, it is believed that these modes at 290 and 670 cm Ϫ1 originated from the macroscopic disorder or vacancy-related defects due to the Mn implantation.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…19 Thus, it is suggested that annealing the implanted GaN at temperatures higher than 800°C resulted in the reduction of implantation-induced disorders in Mn-implanted GaN films, improving magnetic properties of the films. Consequently, it is suggested that optimum annealing temperature ͑Ͻ900°C͒ could be an important parameter in enhancing the ferromagnetism in the Mn-implanted and annealed GaN by suppressing the production of N vacancies…”
Section: B Correlation Between Magnetic Properties and Mn-induced Dementioning
confidence: 99%
“…These extra modes have been attributed to vacancy and vacancy cluster related modes. 22,23 However, after annealing, these peaks are no longer detected and thus the annealing is able to remove most of the implantation damage. It should also be noted that the sapphire substrate is barely detectable in the Raman spectra, indicating that the method is surface sensitive and thus is suitable for characterizing the implanted portion of the GaN.…”
Section: Resultsmentioning
confidence: 99%
“…These modes can be observed when long-range lattice ordering of the host lattice is lost. A relatively strong peak "a" is assigned to a LVM of GaN related to a N vacancy [31]. The peak "b" is assigned to the LVM of Mn occupying the Ga site.…”
Section: Resultsmentioning
confidence: 99%